Trials on tractor front mounted paddy harvester - AHAMMED KABEER T ANAS K. ASSAINAR SHIVAJI K. P SUNIL B; Dr. M Sivaswami (Guide) (Tavanur 1992 Department of Farm Power Machinery and Energy)
prototype unit of the tractor, bharath industrial corporation punjab. front mounted attachment . crop row dividers, star wheel cutter bar assembly
Trials on tractor front mounted paddy harvester